ABO Blood Group and Risk of Colorectal Cancer - Khalili, Hamed (2011)
BACKGROUND: Recent studies have shown an association between non-O blood group and risk of pancreatic cancer. It is unclear whether this association is observed with other gastrointestinal malignancies, including colorectal cancers. METHODS: We examined the relationship between ABO blood group and the risk of incident colorectal cancer in two large prospective cohorts. We calculated hazard ratios using Cox proportional hazard modeling while adjusting for known risk factors of colorectal cancer. RESULTS: During 996,779 person-years of follow-up, we documented 1025 incident cases of colorectal cancers. Compared to individuals with blood group O, the multivariate-adjusted hazard ratios were 1.08 (95% confidence interval [CI] 0.94–1.24) for blood group A, 1.20 (95% CI, 1.00–1.45) for blood group B, and 1.08 (95% CI, 0.85–1.36) for blood group AB. CONCLUSION: In two large prospective cohorts, we did not observe a statistically significant association between ABO blood group and risk of colorectal cancer. IMPACT: These results do not support an association between ABO blood group and risk of colorectal cancer.